2006
DOI: 10.1080/13854040590967603
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of the Rey Word Recognition Test in the Detection of Suspect Effort

Abstract: The Rey Word Recognition Test potentially represents an underutilized tool for clinicians to use in the detection of suspect effort. The present study examined the predictive accuracy of the test by examining the performance of three groups of participants: (a) 92 noncredible patients (as determined by failed psychometric and behavioral criteria and external motive to feign), (b) 51 general clinical patients with no motive to feign, and (c) 31 learning disabled college students. Results demonstrated gender dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Of import to the current study is that the sample included only one participant with ID. The measures and indices used in the study were: (1) the Digit Span Age Corrected Scaled Score (Babikian, Boone, Lu, & Arnold, 2006), (2) RDS, (3) Rey 15-Item plus recognition combination score (Boone, Salazar, Lu, Warner-Chacon, & Razani, 2002), (4) Rey Word Recognition Test (Nitch Boone, Wen, Arnold, & Alfano, 2006), (5) Warrington Recognition Memory Test-Words (Warrington, 1984;Iverson & Franzen, 1994), (6) (Boone, Lu, Back, King, Lee, et al, 2002), and (9) the Finger Tapping Test (Arnold et al, 2005).…”
Section: Effort Tests and Imbedded Validity Indicators: What Does Thementioning
confidence: 99%
“…Of import to the current study is that the sample included only one participant with ID. The measures and indices used in the study were: (1) the Digit Span Age Corrected Scaled Score (Babikian, Boone, Lu, & Arnold, 2006), (2) RDS, (3) Rey 15-Item plus recognition combination score (Boone, Salazar, Lu, Warner-Chacon, & Razani, 2002), (4) Rey Word Recognition Test (Nitch Boone, Wen, Arnold, & Alfano, 2006), (5) Warrington Recognition Memory Test-Words (Warrington, 1984;Iverson & Franzen, 1994), (6) (Boone, Lu, Back, King, Lee, et al, 2002), and (9) the Finger Tapping Test (Arnold et al, 2005).…”
Section: Effort Tests and Imbedded Validity Indicators: What Does Thementioning
confidence: 99%
“…The patient passed most indicators of response bias, with the exception of the b Test (Boone, Lu, & Herzberg, 2002a; a measure requiring rapid letter identification/discrimination), time to repeat three digits and four digits forward on Digit Span (Babikian, Boone, Lu, & Arnold, 2006), and errors on finger agnosia exam. In contrast, she passed effort indicators associated with the cognitive domains of verbal memory-Rey Word Recognition Test (Nitch, Boone, Wen, Arnold, & Alfano, 2006), Warrington Recognition Memory Test -Words (Kim et al, 2010), Rey Auditory Verbal Learning Test equation , Rey Auditory Verbal Learning Test/Rey …”
Section: Cognitive Test Resultsmentioning
confidence: 99%
“…However, emerging data show that test-takers motivated to underperform on exam adopt differing strategies (Boone, 2009;Larrabee, 2004;Nitch et al, 2006;Tan, Slick, Strauss, & Hultsch, 2002) with only 16% failing all measures of response bias administered (Boone, 2009). Osmon and colleagues (Osmon, Plambeck, Klein, & Mano, 2006) observed that simulators feigning reading impairment were better detected by a test specifically developed to identify feigned reading deficits than by a commonly used verbal memory effort indicator (Word Memory Test).…”
Section: Discussionmentioning
confidence: 99%
“…Malingerers are heterogeneous in their strategies for feigning, with some focusing on verbal memory, others on processing speed, others on motor dysfunction, etc. (Boone 2009;Nitch et al 2006;Tan et al 2002); if they only feign in circumscribed neuropsychological domains, they will likely pass SVTs associated with remaining domains. Intact SVT performances in malingerers also occur because they intuit that poor performance on all tests would not be plausible (Johnstone and Cooke 2003).…”
Section: Criticism Of Criterion B: Evidence From Neuropsychological Tmentioning
confidence: 99%